Só de corpo presente: o silêncio tácito sobre cor e relações raciais na formação de professoras no estado do Pará - COELHO, Wilma de Nazaré Baía (2015)
This text diagnoses one of the most serious problems of education in Brazil: the non-tackling of racial discrimination and prejudice. More than just exposing its existence, it analyses one of its sources: the absence of discussion on race, colour and prejudice in the formation of educators in the State of Pará. On the basis of an analysis of the teachers' formation provided by the Institute of Education of the State of Pará, a secular institution which constitutes a reference for teachers' formation in the State of Pará, this work shows that a good part of the teachers' actions are a consequence of a training that did not deal with fundamental aspects, such as the constitution of Brazilian nationality. We conclude that, despite definite advances forged by social activism regarding the issue of racism since the 1960's, the training of teachers is a factor that continues to contribute to the reproduction of stereotypes and prejudice.